Autonomy support and reduced feedback frequency have trivial effects on learning and performance of a golf putting task - McKay, B.; Ste-Marie, D. M. (Human Movement Science, 2020)
Optimizing Performance Through Intrinsic Motivation and Attention for Learning (OPTIMAL) Theory proposes that choices of any kind support an individual's need for autonomy, motivating them to learn and perform motor skills more effectively. Notably, the authors suggest asking learners to choose when to receive feedback in order to increase autonomy. Conversely, the guidance hypothesis predicts an impact of feedback schedule independent of motivational influences. The purpose of this experiment was to compare the relative and combined effects of autonomy and feedback schedule for the acquisition of a golf putting task without vision of results. Autonomy support (autonomy support vs. yoked) and knowledge of results (KR) schedule (100%-KR vs. 50%-faded-KR) were combined in a 2 × 2 factorial design. Participants (N = 56) in the autonomy support groups were asked to choose from three colours of golf balls for each putt during 10 acquisition blocks. Yoked groups were yoked to the golf ball colour choices of their autonomy support group counterparts. Participants in the 100%-feedback schedule groups were provided x- and y-coordinate KR following every putt during acquisition, while participants in the 50%-faded groups received KR after half of their putts, with feedback frequency decreasing over acquisition blocks. All participants completed a 24-h delayed retention and transfer test without KR. The results were somewhat consistent with OPTIMAL Theory yet the effects were not statistically significant and trivially small. The results were inconsistent with the guidance hypothesis.